Digital technologies in routine palliative care delivery: an exploratory qualitative study with health care professionals in Germany - Susann May; Dunja Bruch; Anne Gehlhaar; Felizitas Linderkamp; Kerstin Stahlhut; Martin Heinze; Matthew Allsop; Felix Muehlensiepen (BMC, 2022)
Abstract Objective To explore health care professionals' (HCPs) perspectives, experiences and preferences towards digital technology use in routine palliative care delivery. Methods HCPs (n = 19) purposively selected from a sample of settings that reflect routine palliative care delivery (i.e. specialized outpatient palliative care, inpatient palliative care, inpatient hospice care in both rural and urban areas of the German states of Brandenburg and Berlin) participated in an explorative, qualitative study using semi-structured interviews. Interview data were analyzed using structured qualitative content analysis. Results Digital technologies are widely used in routine palliative care and are well accepted by HCPs. Central functions of digital technologies as experienced in palliative care are coordination of work processes, patient-centered care, and communication. Especially in outpatient care, they facilitate overcoming spatial and temporal distances. HCPs attribute various benefits to digital technologies that contribute to better coordinated, faster, more responsive, and overall more effective palliative care. Simultaneously, participants preferred technology as an enhancement not replacement of care delivery. HCPs fear that digital technologies, if overused, will contribute to dehumanization and thus significantly reduce the quality of palliative care. Conclusion Digital technology is already an essential part of routine palliative care delivery. While generally perceived as useful by HCPs, digital technologies are considered as having limitations and carrying risks. Hence, their use and consequences must be carefully considered, as they should discreetly complement but not replace human interaction in palliative care delivery.